Chiral determination of cinchonine using an electrochemiluminescent sensor with molecularly imprinted membrane on the surfaces of magnetic particles. (19th April 2017) - Yuan, Xingyi; Tan, Yanji; Wei, Xiaoping; Li, Jianping
Abstract: A novel molecular imprinting electrochemiluminescence sensor for detecting chiral cinchonine molecules was developed with a molecularly imprinted polymer membrane on the surfaces of magnetic microspheres. Fe3 O4 @Au nanoparticles modified with 6‐mercapto‐beta‐cyclodextrin were used as a carrier, cinchonine as a template molecule, methacrylic acid as a functional monomer and N, N ′‐methylenebisacrylamide as a cross‐linking agent. Cinchonine was specifically recognized by the 6‐mercapto‐beta‐cyclodextrin functional molecularly imprinted polymer and detected based on enhancement of the electrochemiluminescence intensity caused by the reaction of tertiary amino structures of cinchonine molecules with Ru(bpy)3 2+ . Cinchonine concentrations of 1 × 10 −10 to 4 × 10 −7  mol/L showed a good linear relationship with changes of the electrochemiluminescence intensity, and the detection limit of the sensor was 3.13 × 10 −11  mol/L. The sensor has high sensitivity and selectivity, and is easy to renew. It was designed for detecting serum samples, with recovery rates of 98.2% to 107.6%.